The Many Faces of Internet Marketing (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2017)
In the last decade marketing discipline has been revolutionized. Internet marketing in now considered to be one of the fastest growing branches of marketing theory and practice, which has emerged as a direct response to fast-growing and changing market landscape. The power of the web has transformed both consumer behaviour and lifestyle and traditional marketing strategy path towards completely new patterns that has become an imperative in modern business surroundings. Thus, the intention of this paper is to examine all faces of Internet-based marketing and to highlight all challenges and opportunities that should be addressed today, and in the near future, in the context of Internet as a centre of business operations. Relying on the results of research and analysis in the given field, it is clear that Internet improvements are going to create even more dynamic and challenging environment in just next few years, and that embracing digital marketplace rules and engaging in full range of internet marketing activities is vital for companies across all industries.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.